An hplc method for qualitative and quantitative determination of fosaprepitant in Pharmaceutical products - PRASADA REDDY,; MCS SUBHA, (International Journal of Pharma and Bio Sciences, 2018)
The aim of the present research was to develop and validate a robust HPLC method for quantification related impurities in Fosaprepitant which are the most commonly used antibiotics in intensive care units. 3.4g of K2HPO4 in 1000 ml of water used as buffer solution. Mobile phase A (buffer and acetonitrile 80:20 v/v) and mobile phase B (Acetonitrile and acetonitrile 80:20 v/v) were used as mobile phase. Zorbax Eclipse XDB 250x4.6mm, 5µ column; Flow rate 1.2ml/min, 30°C column temperature, 210 nm were used as chromatographic conditions. Gradient program at 0 min 30% mobile phase B, at 15 min 60%, at 17 min 65%, at 18 min 30%, at 25 min 30%; 7. Diluent: water and acetonitrile 50:50 v/v were applied.Method validation was performed as per ICH Q2 guidance with precision, linearity, accuracy, ruggedness, robustness and specificity. Three known impurities were well separated and quantified. Three impurities were spiked to Fosaprepitant standard, impurity A eluted at12.4min, impurity B at 10.3min and impurity C at 8.0min.Method validation results showed the accuracy and robustness of the HPLC method. Hence, the optimized and validated method can be applied for regular quality control anlaysis.